2022
DOI: 10.3390/ijms23169180
|View full text |Cite
|
Sign up to set email alerts
|

Increased Gene Targeting in Hyper-Recombinogenic LymphoBlastoid Cell Lines Leaves Unchanged DSB Processing by Homologous Recombination

Abstract: In the cells of higher eukaryotes, sophisticated mechanisms have evolved to repair DNA double-strand breaks (DSBs). Classical nonhomologous end joining (c-NHEJ), homologous recombination (HR), alternative end joining (alt-EJ) and single-strand annealing (SSA) exploit distinct principles to repair DSBs throughout the cell cycle, resulting in repair outcomes of different fidelity. In addition to their functions in DSB repair, the same repair pathways determine how cells integrate foreign DNA or rearrange their g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 85 publications
2
4
0
Order By: Relevance
“…Results generated during the above study also support the notion that the suppression of HR activity at high IR doses is a regulated process, delimited but not defined by the 53BP1 and RAD52 activities [157]. The suppression of HR at high IR doses is not an isolated phenomenon, as a separate study utilizing a panel of somatic and lymphoblastic cell lines also demonstrated a pronounced suppression of HR at doses above 2 Gy [167]. Our results also indicated that the process of DNA end resection is uncoupled from HR in terms of IR dose-dependent regulation, as RPA foci formation saturates at much higher By calculating the ratio between RAD51 and γ-H2AX foci, we could evaluate the fraction of DSB engaging HR at any given IR dose (Figure 3C).…”
Section: Repair Pathway Choice By Gauging Dsb Load: Suppression Of Hr...supporting
confidence: 72%
See 3 more Smart Citations
“…Results generated during the above study also support the notion that the suppression of HR activity at high IR doses is a regulated process, delimited but not defined by the 53BP1 and RAD52 activities [157]. The suppression of HR at high IR doses is not an isolated phenomenon, as a separate study utilizing a panel of somatic and lymphoblastic cell lines also demonstrated a pronounced suppression of HR at doses above 2 Gy [167]. Our results also indicated that the process of DNA end resection is uncoupled from HR in terms of IR dose-dependent regulation, as RPA foci formation saturates at much higher By calculating the ratio between RAD51 and γ-H2AX foci, we could evaluate the fraction of DSB engaging HR at any given IR dose (Figure 3C).…”
Section: Repair Pathway Choice By Gauging Dsb Load: Suppression Of Hr...supporting
confidence: 72%
“…Similar PFGE experiments conducted with wild-type G 2 -phase-enriched cell lines, where HR activity is at a maximum, demonstrate repair capacity similar to that of exponentially growing cells [53]. The limited impact of HR on DSB repair in these experiments is further validated in experiments testing G 2 -phase cell populations exposed to a highly specific small molecule inhibitor, VE-821, which impedes HR through the abrogation of ATR activity [167]. Furthermore, we have reported that actively growing mouse embryonic fibroblasts (MEF) that are defective in HR repair, process DSBs with an efficiency similar to that of wild-type cells [169].…”
Section: Repair Pathway Choice By Gauging Dsb Load: Suppression Of Hr...supporting
confidence: 59%
See 2 more Smart Citations
“…DSBs can be repaired by several organized mechanisms to maintain the stability and integrity of the genome [35], which is vital for cell survival. Classical nonhomologous end joining (NHEJ), homologous recombination (HR), alternative end joining (alt-EJ), and single-strand annealing (SSA) represent distinct DSB repair mechanisms [36], of which NHEJ and HR are the most pivotal and common. Post-translational modifications (PTMs) are covalent chemical modifications of proteins that occur after translation, conferring proper activity and biological functions to these proteins.…”
Section: Introductionmentioning
confidence: 99%